2000
DOI: 10.1029/2000gl011700
|View full text |Cite
|
Sign up to set email alerts
|

Possible causes of stratospheric NO2 trends observed at Lauder, New Zealand

Abstract: Abstract.A recently published analysis of slant columns of NO2 observed at twilight at 45øS has identified trends of about 5% /decade between 1980 and 1998. This is twice the trend in tropospheric N20, which is the source of stratospheric NO2. By means of a column photochemical model, we explore the sensitivity of NO2 to the observed trends in stratospheric temperature, 0 3 and H20. The resulting calculated trends in NO 2 are smaller than observed, and we cannot force agreement by varying the ozone or temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…McLinden et al (2001) suggested that the rate of increase in NO y should be about threequarters that of N 2 O due to simultaneous trends in stratospheric ozone and temperature. An increase in column-NO 2 at >5%/decade has been reported (Liley et al, 2000), which is consistent with an increase in NO y combined with a shift in the NO 2 /NO y partitioning due to changes in ozone, temperature, halogens, and possibly aerosol loading over the length of the time series (Fish et al, 2000;McLinden et al, 2001). …”
supporting
confidence: 54%
“…McLinden et al (2001) suggested that the rate of increase in NO y should be about threequarters that of N 2 O due to simultaneous trends in stratospheric ozone and temperature. An increase in column-NO 2 at >5%/decade has been reported (Liley et al, 2000), which is consistent with an increase in NO y combined with a shift in the NO 2 /NO y partitioning due to changes in ozone, temperature, halogens, and possibly aerosol loading over the length of the time series (Fish et al, 2000;McLinden et al, 2001). …”
supporting
confidence: 54%
“…A change in the Dobson-Brewer circulation could also affect the evolution of stratospheric NO 2 (Fish et al, 2000). Cook and Roscoe (2009) recently reported a small, though not significant, increase in the stratospheric circulation of +1.4 ± 3.5 % decade −1 derived from SAOZ NO 2 observations in Antarctic summer.…”
Section: Resultsmentioning
confidence: 99%
“…Using 3-D-Chemical Transport Model calculations, McLinden et al (2001) suggested that the 5 % decade −1 NO 2 trend from 1981 to 1999 results from a 2.5 % decade −1 increase due to rising N 2 O emissions and further 2.5 % decade −1 increase resulting from a decrease in stratospheric ozone. The abundance of NO 2 in the stratosphere can be affected by ozone through the following reaction (Fish et al, 2000):…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the sulphate aerosol influences NO 2 column due to well-known denoxification processes via heterogeneous chemistry. The large eruption of Mount Pinatubo in 1991 led to an increase of the aerosol loading by 2 orders of magnitude resulting in highly enhanced aerosol surface areas and hence in heterogeneous chemical processing in the stratosphere until at least the mid-1990s (Fish et al, 2000). The aerosol contribution varies with the period covered by the time series, notably covering the Mt Pinatubo period.…”
Section: Nomentioning
confidence: 99%